2017
DOI: 10.1002/adma.201701130
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Low Damping and Strong Magnetoelastic Coupling in Epitaxial Spinel Ferrite Thin Films

Abstract: Low-loss magnetization dynamics and strong magnetoelastic coupling are generally mutually exclusive properties due to opposing dependencies on spin-orbit interactions. So far, the lack of low-damping, magnetostrictive ferrite films has hindered the development of power-efficient magnetoelectric and acoustic spintronic devices. Here, magnetically soft epitaxial spinel NiZnAl-ferrite thin films with an unusually low Gilbert damping parameter (<3 × 10 ), as well as strong magnetoelastic coupling evidenced by a gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 57 publications
(180 reference statements)
17
101
0
Order By: Relevance
“…This, however, is also likely to enhance the phonon contribution to the magnetic damping, leading to a correlation between B and α observed in realistic magnetic materials. 49 To characterise the strength of the Fano resonance, we note that the fate of the magnon excited by the incident acoustic wave is decided by the relation between the emission rate Γ R , see Eq. (14), and absorption rate Γ FMR .…”
mentioning
confidence: 99%
“…This, however, is also likely to enhance the phonon contribution to the magnetic damping, leading to a correlation between B and α observed in realistic magnetic materials. 49 To characterise the strength of the Fano resonance, we note that the fate of the magnon excited by the incident acoustic wave is decided by the relation between the emission rate Γ R , see Eq. (14), and absorption rate Γ FMR .…”
mentioning
confidence: 99%
“…To quantify effective damping in coherently strained MAFO(/CCO) thin films, we performed broadband FMR measurements at room temperature in a coplanar waveguide setup using the same procedure as our prior work 16,18 . We show FMR results with external bias magnetic field applied in the film plane along the [100] direction of MAFO(/CCO); essentially identical damping results were obtained with in-plane field applied along [110] 47 .…”
Section: Ferromagnetic Resonance Characterization Of Dampingmentioning
confidence: 99%
“…Low-dissipation spintronic devices become particularly attractive if insulating ferrite thin films with low magnetic damping can serve as sources of magnon spin currents. Such low-damping ferrites include not only epitaxial garnet ferrites (e.g., YIG) [3][4][5][6][7][8][9][10][11] that have been widely used in studies of insulating spintronics [2][3][4][12][13][14][15] , but also coherently strained epitaxial spinel ferrites [16][17][18] with crucial technical advantages over garnets, such as lower thermal budget for crystallization, higher magnon resonance frequencies, and potential to be integrated coherently with other spinels and perovskites with various functionalities [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…15 Previous studies to have attempted to achieve both high Q and high λ m in epitaxial thin films, 16,17 but, it has proven difficult to achieve both conditions simultaneously. 16 Although, Howe et al 18 have recently reported an optimum tradeoff between high Q and λ m for NiZnAl-ferrite.…”
Section: Introductionmentioning
confidence: 99%